The evolution of ethnocentrism revisited: An agent-based model with inductive reasoning - Pedro Vitor Ramos Halbout Carr\~ao; Mariana Wik Atique (EconomiA, 2020)
Studies on the social behavior and cooperation decisions of individuals within and between different ethnic or cultural groups have gained increasing importance in economic sciences, especially in the field of behavioral economics. Axelrod and Hammond (2006) developed an agent-based simulation model to better understand the fundamentals of this phenomenon. Briefly, this model simulates a world with four different neighborhoods, based in a square toroidal lattice shape, where a cell can be inhabited or uninhabited by an agent. The simulation takes 3 stages, Interaction, Reproduction and Death and Placement and get as main result, an ethnocentric agents dominate population based on the path of the agents. The present study aims to broaden the model created by the authors by adding a process of inductive reasoning for the decision making of the agents from the perception of the actions of the others toward him. Our main result are that individuals who understand and interpret part of the environment that are inserted and react inductively to it tend to be more cooperative to the detriment of discriminatory and ethnocentric behavior found in the original model. We also analyze the importance of agent perception in the model and find that agents that perceive and interact with a larger number of other agents tend to be less ethnocentric.
Keywords: C73; Z13; 330; Agent-based model; Behavioral economics; Inductive reasoning; Prisoner's dilemma